We, the King : creating royal legislation in the sixteenth-century Spanish new world / Adrian Masters. - Masters, Adrian, 1988- (Cambridge Latin American studies ;, 2023)
We, the King challenges the dominant top-down interpretation of the Spanish Empire and its monarchs' decrees in the New World, revealing how ordinary subjects had much more say in government and law-making than previously acknowledged. During the viceregal period spanning the post-1492 conquest until 1598, the King signed more than 110,000 pages of decrees concerning state policies, minutiae, and everything in between. Through careful analysis of these decrees, Adrian Masters illustrates how law-making was aided and abetted by subjects from various backgrounds, including powerful court women, indigenous commoners, Afro-descendant raftsmen, secret saboteurs, pirates, sovereign Chiriguano Indians, and secretaries' wives. Subjects' innumerable petitions and labor prompted - and even phrased - a complex body of legislation and legal categories demonstrating the degree to which this empire was created from the "bottom up". Innovative and unique, We, the King reimagines our understandings of kingship, imperial rule, colonialism, and the origins of racial categories.